Industrial Technology Graduates’ Acquired Skills and Competencies from the University - Amado C Gequinto; Do Mads (Journal of Educational Science and Technology (EST), 2019)
Skills and competencies are highly regarded in todays global market. Different agencies specifically those seeking for  technologists, technicians, and engineers, have stressed out that skills and competencies as major components  for individual workers.  This aimed to determine  the relevance and appropriateness of acquired skills and competencies by industrial technology graduates, and determine the extent of use of skills and competencies in the current employment. Review of related literatures and studies have been considered in the realization, understanding, analysis, and interpretation of this research exploration. A descriptive method of research was used with 78 graduates from 2015-2016 and 117 graduates from 2016-2017, who participated in the study survey process. The BatStateU Standardized Questionnaire was used to gather data. A brief interview and talk during the visit of alumni in the university was also considered, as well as the other means of social media like email, facebook, messenger, and text messaging.   Results show that skills and competecnices acquired by industrial technology graduates are all relevant and appropriate.  The study also found that there is some to great extent use of acquired skills and competencies to their current employment. The study implies that the acquired skills and competencies from the university significantly provided the graduates the opportunities ins the national and global markets and industries.